Connection Motivation Control Pressure Blood With Quality Of Life In Hypertension Patients At UPTD Puri Mojokerto Community Health Center - Nada, Alisa Qotrun; Soemah, Eka Nur; Ningsih, Arum Dwi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Motivation to control blood pressure is important for hypertension patients to increase efforts to control blood pressure so that the value... quality of life can be maintained. Lack of stress control motivation blood causes blood pressure control efforts to not run optimally thus causing health problems that reduce the quality of life of hypertensive patients. The purpose of this study was to analyze the relationship between blood pressure control motivation and quality of life in hypertensive patients in UPTD Puri Health Center, Mojokerto Regency. This study uses a quantitative research design with a cross-sectional approach. The population in this study were all hypertensive patients present at Prolanis, as many as 39 patients who were taken using total sampling. Data collection was carried out using a questionnaire. Data analysis was carried out using the Spearman Rho test with SPSS version 21. The results showed that most respondents had a good category of blood pressure control motivation with a good category of quality of life as many as 33 (84.6%). The p-value <0.05 was obtained, which was 0.00 so that Ho was rejected, meaning that there was a relationship between blood pressure control motivation and the quality of life of hypertensive patients. The correlation coefficient value was 0.899, which means that the level of closeness of the relationship in the category is very strong and positive results are interpreted as the better the motivation to control blood pressure, the better the quality of life vice versa.